OPTIMISATION OF HYDROSTATIC THRUST BEARING USING SEQUENTIAL QUADRATIC PROGRAMMING - (:unkn) unknown (SCIBULCOM LTD, 2014)
In this research the efficiency of sequential quadratic programming (SQP) is considered for the optimisation problem of hydrostatic turbogenerator thrust bearing. In this type of turbogenerators, the thrust bearings are designed to permit rotation between parts, while carrying high load on a thin layer of liquid. It is named as hydrostatic thrust bearing on which the fluid is externally pressurised by a pump using electrical energy. The purpose of this study is minimising the pump energy by optimising the design variables among given constraints. There are several methods to optimise this kind of problem but SQP generally gives effective results in shorter time than others. Recently, some researchers used this problem partially and used different cases but only Siddall used full problem to optimise. For that reason, in this paper the Siddalls study is chosen as reference and the results are compared with his results. The problem is optimised by using SQP and obtained results are compared with previous study. It is shown that better results are obtained in shorter time.
Keywords: SQP; optimisation; turbogenerator; thrust bearing; JOURNAL BEARINGS; OPTIMUM DESIGN; PERFORMANCE